Research made easier : a step-by-step process - Cristobal, Amadeo Pangilinan, Jr. (Quezon City, Philippines : C & E Publishing, Inc., 2013)
Especially designed for college students who are required to submit an undergraduate or a "baby" thesis in their major field of study, Research Made Easier: A Step by Step Process expounds on the concepts and principles that underlie the preparation and writing of a research paper. It examines as well the various aspects of the research study from formulating a title, stating the main problem and sub-problems, and devising a methodology, to gathering, presenting, and interpreting data, onto summarizing the findings, drawing conclusions and making recommendations. These discussions are substantiated by authentic examples and excerpts from student theses, and capped by activities and exercises that take students on an experiential research writing process.
Keywords: Research; Research report writing; Research--Methodology